2022
DOI: 10.2478/helm-2022-0032
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infection among rural schoolchildren in Taiz, Yemen: School-based assessment of the prevalence and associated risk factors

Abstract: Summary Yemen is an underdeveloped country plagued by poverty, disease, and social conflicts. Furthermore, most of the population lives in rural areas and is vulnerable to intestinal parasite infections (IPI). School-based cross-sectional studies were conducted between 1 February and 31 March 2019 among schoolchildren in rural communities in the Sabir Almawadim and Almawasit districts of Taiz, southwest Yemen. A structured questionnaire collected information regarding sociodemographic characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
4
2
Order By: Relevance
“…The findings of this study revealed that the overall proportion of intestinal parasites detected among participants was 48%. This finding is lower than what is reported in a previous study conducted in Yemen that documented the frequency rate of parasite infection at 58.7% in Hadramowat [11], 90% in Al-Mahweet [16], 62.7% in Ibb [14], 73.25% in Hajjah [17], 61.85% in Sana'a [18], 51.26% in Taiz [19], and 61.85% in Amran [20]. Moreover, this finding is reported lower in different countries: 29.4% in Ethiopia [21], 46.2% in Egypt [3], 15% in Ghana [22], and 5.3% in Saudi Arabia [23].…”
Section: Discussioncontrasting
confidence: 71%
“…The findings of this study revealed that the overall proportion of intestinal parasites detected among participants was 48%. This finding is lower than what is reported in a previous study conducted in Yemen that documented the frequency rate of parasite infection at 58.7% in Hadramowat [11], 90% in Al-Mahweet [16], 62.7% in Ibb [14], 73.25% in Hajjah [17], 61.85% in Sana'a [18], 51.26% in Taiz [19], and 61.85% in Amran [20]. Moreover, this finding is reported lower in different countries: 29.4% in Ethiopia [21], 46.2% in Egypt [3], 15% in Ghana [22], and 5.3% in Saudi Arabia [23].…”
Section: Discussioncontrasting
confidence: 71%
“…The ndings of this study revealed that the overall proportion of intestinal parasites detected among participants was 48%. This nding is lower than reported in a previous study conducted in Yemen that documented the frequency rate of parasite infection at 58.7% in Hadramowat [11], 90% in Al-Mahweet [16], 62.7% in Ibb [14], 73.25% in Hajjah [17], 61.85% in Sana'a [18], 51.26% in Taiz [19], and 61.85% in Amran [20].…”
Section: Discussioncontrasting
confidence: 68%
“…In Yemen, there's no strategy or program for eradicating or controlling parasitic infections, especially during the civil war since 2014. Yemen has a high prevalence of IPI infection, and the extent of infection varies from place to place, primarily due to poor quality drinking water supply and unsanitary living conditions (Alharazi, 2022;Al-Yousofi et al, 2022). Most previous studies conducted in Yemen involving parasitic infections have focused mainly on preschoolers and schoolchildren (Alharazi, 2021;Alsubaie et al, 2016;Alwabr et al, 2016;Edrees et al, 2022).…”
Section: Introductionmentioning
confidence: 99%